Identification of trait specific accessions from safflower germplasm collected in Maharashtra: Identification of trait specific accessions from safflower germplasm collected in Maharashtra - N MUKTA; PRADUMAN YADAV; DINESH CHAND (Journal of Oilseeds Research, 2023)
A set of 59 safflower germplasm accessions collected during exploration tour to nine districts of Maharashtra during 2017 were evaluated for two seasons (2017-18 and 2018-19) alongwith two checks. Trait specific accessions for seed and oil yield (14) and early flowering (8) were identified for utilization in breeding.